SPP Toolbox : supporting sustainable public procurement in the context of socio-technical transitions - Trindade, Paula (2018)
ABSTRACT: Public procurement can shape production and consumption trends and represents a stimulus for both innovation and diversification in products and services, through a direct increase in demand. In recent years, the interest in demand-side policies has grown and several approaches have emerged, such as Green Public Procurement (GPP), Sustainable Public Procurement (SPP) and Public Procurement of Innovation (PPI), representing strategic goals to be achieved through public procurement. In this context, there is a need to guide and support public organizations in the uptake of GPP, SPP and PPI practices. To respond to the challenges raised by the operationalization of such strategies, this paper proposes a new tool—the SPP Toolbox—for guiding public organizations as they re-think the procurement process, raising their ambitions and broadening their vision, thus changing the organizational approach towards culture, strategies, structures and practices. This toolbox integrates insights from GPP, SPP and PPI objectives and practices, in the context of the emergence of socio-technical transitions. The toolbox coherently links GPP, SPP and PPI, allowing flexibility in terms of goals, yet promoting an increasing complexity of institutionalized practices and skills—from GPP to SPP and then from SPP to PPI, organized in a framework fully integrated into the organizational strategy.